Application of NiFe2O4 nanoparticles towards the detection of ovarian cancer marker - Maghiani, Isabela Bochembusio. [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
In this work, we explored the potential application of NiFe2O4 magnetic nanoparticles in sensing platforms due to their cost-effectiveness and good magnetic properties. The spinel-type metal oxide was prepared using the conventional hydrothermal synthesis method. The structural, morphological, and magnetic properties of the assynthesized NiFe2O4 nanoparticles were discussed. The nanoparticles were functionalized with cystamine, glutaraldehyde, and PVDF and then modified with the CA 125 antibody to obtain the immunosensor. FTIR and electrochemical analyses reveal immobilization of the antibody on the surface of the NiFe2O4 magnetic nanoparticles. The immunosensor developed in this work was made on a printed circuit board, allowing it to be used as a point-of-care device. The immunosensor showed excellent stability, reproducibility, specificity, and selectivity. Our findings are of great significance for developing novel, high-performance point-of-care electro chemical biosensors to be applied in detecting the CA 125 antigen, a widely used biomarker for the prognosis of ovarian cancer

Neste trabalho, explorou-se a potencial aplicação das nanopartículas magnéticas de NiFe2O4 em plataformas de detecção devido a sua relação custo-benefício e propriedades magnéticas. O óxido metálico do tipo espinélio foi preparado pelo método de síntese hidrotérmica convencional. As propriedades estruturais, morfológicas e magnéticas das nanopartículas de NiFe2O4 sintetizadas foram discutidas. As nanopartículas foram funcionalizadas com cisteamina, glutaraldeído e PVDF e, posteriormente, modificadas com o anticorpo CA 125 para obtenção do imunossensor. Análises de FTIR e eletroquímicas revelam a imobilização do anticorpo na superfície das nanopartículas magnéticas de NiFe2O4. O imunossensor desenvolvido neste trabalho foi confeccionado em uma placa de circuito impresso, permitindo sua utilização como dispositivo point-of-care. O imunossensor apresentou excelente estabilidade, reprodutibilidade, especificidade e seletividade. Nossas descobertas são relevantes para o desenvolvimento de novos biossensores eletroquímicos de alto desempenho para serem aplicados na detecção do antígeno CA 125, um biomarcador amplamente utilizado para o prognóstico do câncer de ovário.
Aplicação de nanopartículas de NiFe2O4 na detecção do marcador de câncer de ovário
Keywords: Nanostructures; Oxides; Chemical synthesis; Magnetic properties; Electrochemical properties; Nanoestrutura; Óxidos; Biossensores